2019
DOI: 10.3389/fmars.2019.00108
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure and Functionality in the Deep Sea Floor: Evaluating the Causes of Spatial Heterogeneity in a Submarine Canyon System (NW Mediterranean, Spain)

Abstract: Understanding community assembly and processes driving diversity in deep-sea environments is a major challenge in marine microbial ecology. The deep sea represents the largest ecosystem on Earth, but its remoteness makes the microbial community composition and functionality largely unknown. Moreover, microbial-focused studies comparing different deep-sea habitats like dynamic submarine canyons and slope ecosystems altogether are rare. The present work aims to study the deep-sea seafloor microbial communities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…It is well known that the Ligurian Sea, the Gulf of Lion and the Catalan Shelf are regions of enhanced vertical dynamics, where dense coastal water can overflow the shelves and cascade down the slope, favoring the transport of particulate matter into the mesopelagic layer (The MERMEX Group, 2011). In particular, submarine canyons constitute a preferential way through which deep-sea environments are exposed to particulate matter fluxes generated by coastal and pelagic productivity (Román et al, 2019) or by the resuspension of sediments (Arjona-Camas et al, 2019). As a result of this vertical mixing, an enhanced reduction in heat and salt contents of IW occurs indicating that, at the end of this part of the path, internal biogeochemical processes are not the major driver of its biogeochemical evolution anymore.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the Ligurian Sea, the Gulf of Lion and the Catalan Shelf are regions of enhanced vertical dynamics, where dense coastal water can overflow the shelves and cascade down the slope, favoring the transport of particulate matter into the mesopelagic layer (The MERMEX Group, 2011). In particular, submarine canyons constitute a preferential way through which deep-sea environments are exposed to particulate matter fluxes generated by coastal and pelagic productivity (Román et al, 2019) or by the resuspension of sediments (Arjona-Camas et al, 2019). As a result of this vertical mixing, an enhanced reduction in heat and salt contents of IW occurs indicating that, at the end of this part of the path, internal biogeochemical processes are not the major driver of its biogeochemical evolution anymore.…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of this study is the lack of geochemical data on sediment cores, since the data on the environmental variables of the overlying water column are not sufficient to explain what is happening in the vertical gradient of sediments. Some studies have shown large variations in physicochemical conditions in the profile of deep-sea sediments (Roy et al, 2012;D'Hondt et al, 2015;Román et al, 2019). Therefore, it will be necessary to continue exploring in more detail the variations in fungal communities that occur along the vertical gradient of sediment profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, what is known about the microbial ecology in deep-sea sediments is mainly about bacteria and archaea ( Edgcomb et al, 2011 ; Nagano and Nagahama, 2012 ; Dekas et al, 2016 ; Xu et al, 2018 ). Therefore, detailed knowledge of deep-sea fungi is required to understand better the overall fungal contribution to marine food webs and biogeochemical cycles at the global scale ( Manohar and Raghukumar, 2013 ; Barone et al, 2018 ; Drake and Ivarsson, 2018 ; Grossart et al, 2019 ; Román et al, 2019 ; Hassett et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the homogeneity or heterogeneity of horizons could be related to the characteristics of the sampled habitat, but also with the sedimentation time. It will be necessary to further explore in more detail the variations that occur at the micro-scale in fungal communities in sediment profiles, as has been done to study variations in the physicochemical conditions of sediments in other deep-sea waters (Roy et al, 2012; D’Hondt et al, 2015; Román et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is crucial to study fungal diversity and ecology in deep-sea waters, for which there is a paucity of studies compared to the rest of the ocean. Detailed knowledge of deep-sea fungi is required to understand better the overall fungal contribution to marine food webs and biogeochemical cycles at the global scale (Manohar and Raghukumar, 2013; Barone et al, 2018; Drake and Ivarsson, 2018; Grossart et al, 2019; Román et al, 2019; Hassett et al, 2020).…”
Section: Introductionmentioning
confidence: 99%